Eksistensi AAUPB di Indonesia dan Yurisprudensinya dalam Perkara TUN - Yasin, Ikhsan Fatah (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: This article discusses the General Principles of Good Governance (AAUPB). It has a long journey from the beginning of its coming in the Netherland to its application in Indonesia today. AAUPB, which previously was only in theoretical realm, it changes into Law No. 30 of 2014 today. The principles contained in the law are legal certainty; expediency; impartiality; accuracy; not to abuse authority; openness; public interest; and good service. In addition to these principles, we can also use other principles as far as they become the basis for the judges' judgments that have permanent legal force. In various cases, the basis of the claim of AAUPB does not stand alone but it is also juxtaposed with violations of statutory regulations. The Supreme Court verdict has become a jurisprudence between Suhaili Saun (shareholder in PT Volex Batamindah) and the Chairman of BKPM, although the plaintiff also argued that violating the AAUPB namely the principle of legal certainty, the defendant also violated article 2 letter b of Law No. 1 of 1967 about Foreign Investment. In the case of the dismissal of Bripda Helga Musa Sitepu by the Head of the North Sumatra Regional Police, the decree has violated article 2 paragraph 2 letter d and article 11 paragraph 1 of KAPOLRI regulation No. 8 of 2006 and was contrary to the principle of the district. Keywords: AAUPB, Jurisprudence, State Administration Abstrak: Artikel ini membahas tentang Asas-Asas Umum Pemerintahan yang Baik (AAUPB), AAUPB memiliki perjalanan yang panjang dari awal kelahirannya di Belanda sampai penerapanya di Indonesia dewasa ini. AAUPB pada awal mulanya hanya berada dalam ranah teoritis baru kemudian masuk dalam undang-undang hingga AAUPB mendapatkan posisi yang sangat penting dalam UU No. 30 Tahun 2014, asas yang terdapat dalam undang-undang tersebut meliputi asas kepastian hukum; kemanfaatan; ketidakberpihakan; kecermatan; tidak menyalahgunakan kewenangan; keterbukaan; kepentingan umum; dan pelayanan yang baik. Selain asas-asas tersebut, bisa juga menggunakan asas lain selama dijadikan dasar penilaian hakim dalam putusan yang sudah mempuyai kekuatan hukum tetap. Dalam berbagai kasus, dasar gugatan karena AAUPB tidak berdiri sendiri tapi juga disandingkan dengan pelanggaran peraturan perundang undangan. Dalam putusan kasasi MA yang telah menjadi yurisprudensi antara Suhaili Saun (pemegang saham di PT Volex Batam Indah) dengan Ketua BKPM, meskipun penggugat mendalilkan juga bahwa selain melanggar AAUPB yaitu asas kepastian hukum, tergugat juga melanggar pasal 2 huruf b UU No. 1 Tahun 1967 tentang Penanaman Modal Asing. Dalam kasus pemberhentian Bripda Helga Musa Sitepu oleh Kepala Kepolisian Daerah Sumatera Utara, surat keputusan tersebut melanggar pasal 2 ayat 2 huruf d dan pasal 11 ayat 1 peraturan KAPOLRI No. 8 Tahun 2006 dan bertentangan dengan asas kceramatan. Kata kunci: AAUPB, Yurisprudensi, Administrasi Negara